Exploring perceptional typology of social media quitters and associations among self-esteem, personality, and motivation. Issue 2 (25th January 2022) - Kim, Jin-Young
ABSTRACT: This study examined why people voluntarily left social media and organised their reasons into perceptional typology. Additionally, it explored relationships among perceptional types, self-esteem, motivation, and personality traits. This study utilised Q methodology, a combination of qualitative and quantitative research methods that is ideal for analysing subjective elements like complex human perceptions or opinions in any situation. Fifty persons in their twenties who voluntarily closed or deactivated their social media account(s) for more than six months were recruited in Korea. Those who left social media of their own accord were sorted into four types. Significant differences in self-esteem and personality traits between cognitive types were also found. This study gave novel descriptive stories of those who quit social media, and categorised the opinions of those who voluntarily closed their accounts. This study extended previous research on social media fatigue and systematically analysed actual quitters' perceptions based on ample discourse; it will theoretically contribute to the development of measuring scales and an understanding of the complexity of social media fatigue. For practical application, social media companies should pay a lot of attention to social media fatigue and quitters, come up with ways to minimise adverse effects and establish growth strategies.